Planar C-Band Antenna with Electronically Controllable Switched Beams - Mariano Barba; Juan E. Page; Jose A. Encinar (International Journal of Antennas and Propagation)
The design, manufacturing, and measurements of a switchable-beam antenna at 3.5 GHz for WLL or Wimax base station antennas in planar technology are presented. This antenna performs a discrete beam scan of a 60∘ sector in azimuth and can be easily upgraded to 5 or more steps. The switching capabilities have been implemented by the inclusion of phase shifters based on PIN diodes in the feed network following a strategy that allows the reduction of the number of switches compared to a classic design. The measurements show that the design objectives have been achieved and encourage the application of the acquired experience in antennas for space applications, such as X-band SAR and Ku-band DBS.